Model Pembelajaran Kooperatif Tipe Snowball Throwing untuk Meningkatkan Hasil Belajar Siswa Tentang Siklus Air - Nurjannah Nurjannah; Fajar Fajar; Yupitasari Yupitasari (Universtas Negeri Makassar, 2023)
This research is motivated by the low learning outcomes of students in class V. This research is a classroom action research (CAR) and uses a qualitative approach. Based on the research data in cycles I and II, the results of the research cycle I showed that the learning process was in good qualification (B), student activities were in sufficient qualification (C) and the learning outcomes test was in sufficient qualification (C) and for the cycle II shows that the learning process is in good qualification (B), student activities are in good category (B) and student learning outcomes are in good qualification (B). Based on the results of the study, it can be concluded that the application of the Snowball throwing type of cooperative learning model can improve the process and student learning outcomes about the water cycle for fifth grade students of UPT SD Negeri 6 Arawa, Sidrap Regency